Application of a mitochondrial DNA control region frequency database for UK domestic cats. (March 2017) - Ottolini, Barbara; Lall, Gurdeep Matharu; Sacchini, Federico; Jobling, Mark A.; Wetton, Jon H.
Highlights: Mitochondrial control region variation is reported for 152 English cats. A globally rare DNA variant was found in cat hairs on a murder victim. Cat population from crime vicinity genetically similar to rest of country. English population similar to US but very different to European cats. Relevant database frequency estimates showing rarity (2%) helped secure conviction. Abstract: DNA variation in 402 bp of the mitochondrial control region flanked by repeat sequences RS2 and RS3 was evaluated by Sanger sequencing in 152 English domestic cats, in order to determine the significance of matching DNA sequences between hairs found with a victim's body and the suspect's pet cat. Whilst 95% of English cats possessed one of the twelve globally widespread mitotypes, four new variants were observed, the most common of which (2% frequency) was shared with the evidential samples. No significant difference in mitotype frequency was seen between 32 individuals from the locality of the crime and 120 additional cats from the rest of England, suggesting a lack of local population structure. However, significant differences were observed in comparison with frequencies in other countries, including the closely neighbouring Netherlands, highlighting the importance of appropriate genetic databases when determining the evidential significance of mitochondrial DNA evidence.